2000
DOI: 10.1042/bj3460305
|View full text |Cite
|
Sign up to set email alerts
|

HIV-2 protease is inactivated after oxidation at the dimer interface and activity can be partly restored with methionine sulphoxide reductase

Abstract: Human immunodeficiency viruses encode a homodimeric protease that is essential for the production of infectious virus. Previous studies have shown that HIV-1 protease is susceptible to oxidative inactivation at the dimer interface at Cys-95, a process that can be reversed both chemically and enzymically. Here we demonstrate a related yet distinct mechanism of reversible inactivation of the HIV-2 protease. Exposure of the HIV-2 protease to H2O2 resulted in conversion of the two methionine residues (Met-76 and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Previously described forms of PMSR also depend on a reductant for activity, with thioredoxin most likely to be the endogenous reductant (Brot et al ., 1981; Moskovitz et al ., 1996). A functional restoration of activity, as seen for the chaperone‐like activity of Hsp21 in Figure 4, has previously been shown for α‐1‐proteinase inhibitor (Abrams et al ., 1981), calmodulin (Sun et al ., 1999) and the HIV‐2 protease (Davis et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously described forms of PMSR also depend on a reductant for activity, with thioredoxin most likely to be the endogenous reductant (Brot et al ., 1981; Moskovitz et al ., 1996). A functional restoration of activity, as seen for the chaperone‐like activity of Hsp21 in Figure 4, has previously been shown for α‐1‐proteinase inhibitor (Abrams et al ., 1981), calmodulin (Sun et al ., 1999) and the HIV‐2 protease (Davis et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the accumulation of methionine sulfoxides in calmodulin from brains of aging rats is accompanied by a decrease in the ability of calmodulin to activate the plasma membrane Ca‐ATPase (Gao et al ., 1998). Another interesting example is the oxidation‐induced inactivation of a protease in two different forms of the human infectious virus (HIV), HIV‐1 and HIV‐2 (Davis et al ., 2000). In the HIV‐1 protease, inactivation is mediated by glutathionylation of cysteine residue 95, an oxidative cross‐linking reaction between glutathione and the cysteine residue, forming a disulfide bridge.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidized β-casein Measured 1.6 ± 0.2 18.6 ± 6.0 90,000 Corrected 2 37.2 ± 12.0 45,000 1 Considering that only the S-diastereomer serve as substrates for DorA reductase [28] and assuming that the R-diastereomer does not act as inhibitor, the K M values were divided by 2. 2 As the ESI-MS analysis indicated that 2 MetO are available substrate for DorA (Figure 1), the K M value was multiplied by 2.…”
Section: Substratementioning
confidence: 99%
“…Either free or included in proteins, the sulfur containing amino acid methionine (Met) can be oxidized to methionine sulfoxide (MetO) which exists as two diastereomers, methionine-S-sulfoxide (Met-S-O) and methionine-R-sulfoxide (Met-R-O) [1]. Formation of MetO in proteins was shown to alter their function in numerous ways, from damageable effects for their activity and stability, to controlled regulation of enzyme activity and protein-protein interactions [2][3][4][5][6]. Contrary to oxidative modifications of most other amino acids, the oxidation of Met into MetO in proteins is reversible thanks to methionine sulfoxide reductase (Msr) enzymes, which are present in all organisms across the tree of life, with few exceptions [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur‐containing methionine residues in living organisms are susceptible to oxidation and can be transformed by exogenous and endogenous reactive oxygen species (ROS) to the corresponding methionine sulfoxide . This oxidative damage to methionine can disrupt the function of a variety of proteins . On the other hand, specific oxidation of methionine to methionine sulfoxide in proteins can also act as a gain‐of‐function post‐translational modification .…”
Section: Introductionmentioning
confidence: 99%